Models describing the degradation of functional parameters of electronic devices based on the Weibull–Gnedenko distribution - Borovikov, Sergei; Shneiderov, Evgeni; Burak, Irina (Publishing House of Lviv Polytechnic National University, 2016)
The authors offer the possibility for obtaining the mathematical model of degradation of a functional parameter in the form of conditional density of its distribution over a given operating time period on the basis of the 3-parametric Weibull–Gnedenko distribution. This model provides reliability prediction errors for samples of electronic devices smaller, than the errors after using the degradation model based on normal distribution of the functional parameter. Автори пропонують можливість отримання математичної моделі деградації функціонального параметра у вигляді умовної густини його 3-параметричного розподілу Вейбула–Гнеденка. Ця модель забезпечує похибку прогнозування надійності для зразків електронних приладів, яка є меншою, ніж похибки після використання моделі деградації на основі нормального розподілу функціонального параметра.
Моделі для опису деградації функціональних параметрів електричних приладів на основі розподілу Вейбула–Гнеденка
Keywords: degradation model of parameter; reliability prediction of electronic devices; semiconductor devices; experiment for reliability prediction